Genome-wide Identification and Expression Analysis of RcMYB Genes in Rhodiola crenulata - Xu, Binjie; Chen, Bang; Qi, Xiaoli; Liu, Shunli; Zhao, Yibing; Tang, Ce; Meng, Xianli (Frontiers in Genetics, 2022)
Modern research has proved that the main medicinal component of Rhodiola crenulata, which has a wide range of medicinal value, is its secondary metabolite salidroside. MYB transcription factor family is widely involved in regulating gene expression in plants, so a genome-wide identification and analysis for this family in R. crenulata is worth to conduct. In this research, Genome-wide analysis identified 139 MYB genes based on conserved domains in the R. crenulata genome, and 137 genes were used to construct a phylogenetic tree and modified with expression files to reveal evolutionary characteristics. Physical and chemical characteristics, gene structure, and conserved motif analysis were also used to further analyze RcMYBs. Additionally, cis-acting elements related to transcription, hormone, and MYB binding were found in the promoter region of the selected RcMYBs. Four RcMYBs were cloned, sequenced, and their gene expression pattern was analyzed for further analysis of their functions. The research results lay a foundation for further research on the function of RcMYB and R. crenulata.